Effect of the Gallium and Vanadium on the Dibenzothiophene Hydrodesulfurization and Naphthalene Hydrogenation Activities Using Sulfided NiMo-V2O5/Al2O3-Ga2O3 (2020)
The effect of Ga and V as support-modifier and promoter of NiMoV/Al2O3-Ga2O3 catalyst on hydrogenation (HYD) and hydrodesulfurization (HDS) activities was studied. The catalysts were characterized by elemental analysis, textural properties, XRD, XPS, EDS elemental mapping and High-resolution transmission electron microscopy (HRTEM). The chemical analyses by X-ray Fluorescence (XRF) and CHNS-O elemental analysis showed results for all compounds in agreement, within experimental accuracy, according to stoichiometric values proposed to Mo/Ni = 6 and (V+Ni)/(V+Ni+Mo) = 0.35. The sol-gel synthesis method increased the surface area by incorporation of Ga3+ ions into the Al2O3 forming Ga-O-Al bonding; whereas the impregnation synthesis method leads to decrease by blocking of alumina pores, as follows NiMoV/Al-Ga(1%-I)< NiMoV/Al-Ga(1%-SG) < NiMo/Al2O3 < Al2O3-Ga2O3(1%-I) < Al2O3-Ga2O3(1%-SG) < Al2O3, propitiating Dp-BJH between 6.18 and 7.89 nm. XRD confirmed a bulk structure typical of (NH4)4[NiMo6O24H6]•5H2O and XPS the presence at the surface of Mo4+, Mo6+, NixSy, Ni2+, Ga3+ and V5+ species, respectively. The EDS elemental mapping confirmed that Ni, Mo, Al, Ga, V and S are well-distributed on Al2O3-Ga2O3(1%-SG) support. The HRTEM analysis shows that the length and stacking distribution of MoS2 crystallites varied from 5.07 to 5.94 nm and 2.74 to 3.58 with synthesis method (SG to I). The results of the characterization sulfided catalysts showed that the synthesis method via impregnation induced largest presence of gallium on the surface influencing the dispersion V5+ species, this effect improves the dispersion of the MoS2 phase and increasing the number of active sites, which correlates well with the dibenzothiophene HDS and naphthalene HYD activities. The dibenzothiophene HDS activities with overall pseudo-first-order rate constants’ values (kHDS) from 1.65 to 7.07 L/(h·mol·m2 ) follow the order: NiMoV-S/Al-Ga(1%-I) < NiMo-S/Al2O3 < NiMoV-S/Al-Ga(1%-SG), whereas the rate constants’ values (k) of naphthalene HYD from 0.022 to 2.23 L/(h·mol·m2 ) as follow: NiMoV-S/Al-Ga(1%-SG) < NiMo-S/Al2O3 < NiMoV-S/Al-Ga(1%-I). We consider that Ga and V act as structural promoters in the NiMo catalysts supported on Al2O3 that allows the largest generation of BRIM sites for HYD and CUS sites for DDS.